Synthesis of indium oxi-sulfide films by atomic layer deposition: The essential role of plasma enhancement - Bugot, Cathy; Schneider, Nathanaëlle; Lincot, Daniel; Donsanti, Frédérique (Beilstein Journal of Nanotechnology, 2013)
This paper describes the atomic layer deposition of In2(S,O)3 films by using In(acac)3 (acac = acetylacetonate), H2S and either H2O or O2 plasma as oxygen sources. First, the growth of pure In2S3 films was studied in order to better understand the influence of the oxygen pulses. X-Ray diffraction measurements, optical analysis and energy dispersive X-ray spectroscopy were performed to characterize the samples. When H2O was used as the oxygen source, the films have structural and optical properties, and the atomic composition of pure In2S3. No pure In2O3 films could be grown by using H2O or O2 plasma. However, In2(S,O)3 films could be successfully grown by using O2 plasma as oxygen source at a deposition temperature of T = 160 °C, because of an exchange reaction between S and O atoms. By adjusting the number of In2O3 growth cycles in relation to the number of In2S3 growth cycles, the optical band gap of the resulting thin films could be tuned.
Keywords: atomic layer deposition; buffer layer; indium oxi-sulfide; plasma enhancement; thin film solar cells